Cerebrospinal fluid liquid biopsy for detecting somatic mosaicism in brain. Issue 1 (28th January 2021) - Ye, Zimeng; Chatterton, Zac; Pflueger, Jahnvi; Damiano, John A; McQuillan, Lara; Harvey, A Simon; Malone, Stephen; Do, Hongdo; Maixner, Wirginia; Schneider, Amy; Nolan, Bernadette; Wood, Martin; et al.
Abstract: Brain somatic mutations are an increasingly recognized cause of epilepsy, brain malformations, and autism spectrum disorders and may be a hidden cause of other neurodevelopmental and neurodegenerative disorders. At present, brain mosaicism can only be detected in the rare situations of autopsy or brain biopsy. Liquid biopsy using cell-free DNA derived from cerebrospinal fluid (CSF) has detected somatic mutations in malignant brain tumors. Here we asked if CSF liquid biopsy can be used to detect somatic mosaicism in non-malignant brain diseases. First, we reliably quantified CSF cell-free DNA in twenty eight patients with focal epilepsy and twenty eight controls using droplet digital PCR. Then, in three patients we identified somatic mutations in CSF: in one patient with subcortical band heterotopia the LIS1 p. Lys64* variant at 9.4% frequency; in a second patient with focal cortical dysplasia the TSC1 p. Phe581His*6 variant at 7.8% frequency; and in a third patient with ganglioglioma the BRAF p. Val600Glu variant at 3.2% frequency. To determine if CSF cell-free DNA was brain-derived, whole-genome bisulfite sequencing was performed and brain-specific DNA methylation patterns were found to be significantly enriched (p = 0.03). Our proof of principle study shows that CSF liquid biopsy is valuable in investigating mosaic neurological disorders where brain tissue is unavailable. Graphical Abstract: